Helicobacter pylori infection manifesting as Hypereosinophilic syndrome and immune thrombocytopenia complicated by portal vein thrombosis and ischemic colitis - Awni Alshurafa (15468195) (2022)
Hypereosinophilic syndromes (HES) are a group of uncommon disorders characterized by persistent eosinophils overproduction which can lead to tissue damage and organs dysfunction secondary to eosinophils tissue infiltration and inflammatory mediators’ release. Causes of secondary HES include parasitic infection, some solid tumors, underlying connective tissue disease, allergic conditions and T cell lymphoma. Helicobacter pylori (H. pylori) has been reported only once as a cause of secondary HES in the literature. We report the second case of H. pylori infection in 29-year-old male patient who presents with HES and secondary Immune thrombocytopenic purpura (ITP). This case is different from the first reported case by the presence of HES complication on presentation manifesting as portal vein thrombosis, which was further complicated by ischemic colitis. H, pylori eradication therapy alone was successful in a resolution of hypereosinophilia and platelets recovery without the need of corticosteroids or any other treatment. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2022.e01451